Pengaruh Lingkungan Keluarga terhadap Hasil Belajar Akuntansi Kelas X di SMK Jakarta Timur 1 - Melya Indrianti (INTELEKTIUM, 2022)
This study aims to determine the effect of the family environment on the learning outcomes of class X accounting students at SMK East Jakarta 1. The type of research used is quantitative method. The population of this study were students of class X Accounting with a total sample of 54 students. Data collection uses questionnaires, interviews and documentation of student learning outcomes taken from the odd semester midterm exam scores for 2021/2022. As for the data analysis technique using simple linear regression analysis and t-test. The results showed that the family environment affected student learning outcomes as indicated by the r value of 0.77 and the coefficient of determination (r2) 0.5929%, tcount of 8.701 and ttable of 1.674 (tcount > ttable), then Ho was rejected and H1 was accepted. . This shows that 59.29% of students' learning outcomes are influenced by the family environment. So it can be concluded that there is a significant influence between the family environment on the learning outcomes of class X accounting students at SMK East Jakarta 1.